2008
DOI: 10.1063/1.2970993
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of ultraviolet emissions in Tm-doped AlN using above band gap excitation

Abstract: We report on dynamics of ultraviolet (UV) emissions using above band gap excitation in Tm-doped AlN epilayers grown by solid-source molecular beam epitaxy. The UV and visible photoluminescence (PL) spectra were measured using the frequency quadrupled output from a Ti:sapphire laser. In the UV region, dominant emissions at 298 and 358 nm were observed under 197 nm excitation. Temperature dependence of the PL intensities of these emission lines reveals a binding energy of ∼150 meV. The quenching of the UV emissi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…RE emissions in the visible and UV spectral region were reported for Pr, Eu, Tb, Tm, and Gd doped AlN. [6][7][8][9][10][11] Equally interesting are the recently reported magnetic properties of RE implanted AlN showing ferromagnetism at room temperature ͑RT͒. 12 Both optical and magnetic properties of implanted AlN will be strongly dependent on the structural quality of the films and defects produced during the implantation.…”
Section: Introductionmentioning
confidence: 93%
“…RE emissions in the visible and UV spectral region were reported for Pr, Eu, Tb, Tm, and Gd doped AlN. [6][7][8][9][10][11] Equally interesting are the recently reported magnetic properties of RE implanted AlN showing ferromagnetism at room temperature ͑RT͒. 12 Both optical and magnetic properties of implanted AlN will be strongly dependent on the structural quality of the films and defects produced during the implantation.…”
Section: Introductionmentioning
confidence: 93%
“…Temperature dependence of emission intensity is usually fitted by the following formula. ,, where I 0 is the intensity at T = 0 K, A is fitting parameter, k is Boltzmann constant, and E a is the activation energy for the thermal quenching process. The fitting curves to our data are shown in Figure e,f.…”
Section: Resultsmentioning
confidence: 99%
“…They reported a broad emission band near 300 nm for alloys with x Ͼ 0.81. Nepal et al 24 examined the UV emission from AlN:Tm samples using above-bandgap excitation at 197 nm and found sharp emission lines at 298 and 356 nm, as seen in Fig. 1͑a͒.…”
mentioning
confidence: 98%
“…Previously, we reported that the measured energy level of the RESI trap was 1.50 eV in AlN:Tm. 24 Thus, the thermal quenching of the deep UV transitions in Al x Ga 1−x N : Tm is due to thermal dissociation of the excitons bound to RESI charge traps at 1.50 and 0.57 eV for alloys with x = 1 and 0.81, respectively. From the present data and previous experimental results we have constructed a schematic energy level model, as shown in Fig.…”
mentioning
confidence: 99%